The Effect of Digital Flashcards on Students’ Reading Comprehension: A Quantitative Study - Putu Devita Kiranaputri Suada; Ni Nyoman Padmadewi; Kadek Sintya Dewi (English Education Department STKIP Agama Hindu Singaraja, 2025)
This study aims to investigate using digital flashcards as a learning tool for tenth-grade SMA Negeri 1 Singaraja students' instruction in reading comprehension. Given the challenges students have in their reading comprehension, integrating digital learning tools can be a successful approach for raising engagement and comprehension among them. Two groups—an experimental group guided using digital flashcards and a control group guided using conventional media—were part of a quasi-experimental research design. A post-test was done to assess how digital flashcards might affect students' reading comprehension. The gathered data, which included homogeneity tests, normality tests, and an independent t-test to determine statistical significance, was analysed using SPSS. The results showed that the experimental group did noticeably better than the control group, implying that digital flashcards improve the reading comprehension of students. According to the findings, digital flashcards can be quite a useful and interesting tool for raising students' reading competency. The study adds to the growing corpus of studies on digital learning media and provides useful guidelines for teachers on including technology in English language instruction.